Alternative Risk Transfer and Insurance-Linked Securities: Trends, Challenges and New Market Opportunities - Semir Ben Ammar; Alexander Braun; Martin Eling (Verlag Institut für Versicherungswirtschaft der Universität St. Gallen, 2015)
Due to their relatively high yields and low return correlations with traditional asset classes, insurance-linked securities (ILS) are often described as an attractive investment opportunity. Yet, the investor base for ILS is largely dominated by a few specialized investment managers. The aim of this study is to analyze advantages and disadvantages, the current market development and the decision-making processes that drive the demand for this aspiring asset class. To reach this aim, we first review the existing knowledge on ILS instruments and markets, then present results of a new international survey among ILS investors and finally, based on the results of the first and second step, derive implications for the future development of ILS.
Keywords: 330; Insurance-Linked Securities; Kapitalmarktrendite; Risikoprämie; Anlageverhalten; Finanzmarkt; Welt